Strategies in technical loss reduction and it's impact on harmonic performance of distribution network - Au M.T.; Anthony T.M.; Mohamad M. (2023)
This paper presents strategies in the reduction of technical losses of utility distribution network and analyze its impact on harmonic performance. A comprehensive estimation of technical losses of a distribution network is performed using analytical spreadsheet to determine loss level of major network components i.e, medium voltage (MV) feeders (33 kV and 11 kV), transformers and low voltage (LV) network against variations in load current and reactive power. Results based on simulation studies show that power factor correction capacitors (pfcc) are effective means of mitigating technical losses, particularly in LV network which supply large number of small and medium to residential and/or commercial loads. Pfcc which are appropriately sized and strategically placed in LV network is able to reduce technical losses by a significant margin without jeopardizing harmonic performance. 2009 IEEE.